Management of occult hepatitis B virus infection: An update for the clinician - Lledó, José Luis (Baishideng Publishing Group Co., Limited, 2011)
Occult hepatitis B virus (HBV) infection (OBI) is defined by the presence of HBV DNA in the liver tissue of individuals who test negative for hepatitis B surface antigen (HBsAg). Patients who have recovered from acute hepatitis B can carry HBV genomes for a long time and show histological patterns of mild necro-inflammation, even fibrosis, years after the resolution of acute hepatitis, without showing any clinical or biochemical evidence of liver disease. At least in conditions of immunocompetence, OBI is inoffensive itself, but when other relevant causes of liver damage are present it might make the course of the liver disease worse. The risk of HBV transmission through transfusion is related to blood donations negative for HBsAg that have been collected during the pre-seroconversion period or during chronic OBI. Use of HBV nucleic acid amplification testing and multivalent anti-HBs antibodies in the HBsAg assays is recommended for detection of true and false OBI, respectively. It is not known if prior hepatitis B immunization with an optimal anti-HBs response in cases of HBV transmission through organ transplantation can effectively modulate or abort the infection. Use of antiviral agents as prophylaxis in patients with serological evidence of past HBV infection prevents reactivation of OBI after transplantation in most cases. Reactivation of OBI has been observed in other conditions that cause immunosuppression, in which antiviral therapy could be delayed until the HBV DNA or HBsAg becomes detectable. OBI might contribute to the progression of liver fibrosis and hepatocellular carcinoma development in patients with chronic liver disease.